Analisis Psikologi Tokoh Acha Daam Novel Mariposa Kajian Psikoanalisis Sigmun Freud - Slama Slama; Ahmad Ilzamul Hikam (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study discusses the character of Acha in the novel Mariposa by Luluk HF using Sigmund Freud's psychoanalytic approach. Acha is described as a teenager who is persistent in pursuing love, but has a complex inner conflict. This study was conducted because psychological issues, especially in teenagers, are very relevant in modern life. The method used is a qualitative-descriptive approach with Freud's structural analysis of personality, namely id, ego, and superego. In this study, Acha shows the dominance of the id when expressing love impulsively, the ego when adjusting to the bitter reality, and the superego when choosing honesty even though it is painful. The presence of supporting characters also strengthens Acha's psychological dynamics in the story. The results of the study show that Acha's internal conflict is a reflection of the struggle between desire, reality, and morality, and describes the process of maturing teenage characters. This study is expected to provide a deeper understanding of psychological dynamics in literary works and their relevance to the lives of teenagers today.